Pengaruh Efektivitas Penggunaan, Kepercayaan dan Kualitas Sistem Informasi Akuntansi pada Kinerja Karyawan - Sari, Ni Luh Putu Dwi Gita; Putra, I Made Pande Dwiana (E-Jurnal Akuntansi; Vol 26 No 1 (2019), 2019)
The development accounting information system has penetrated into various fields of life, one of which is utilized for the progress of the company. The sustainability of a company is determined by the performance of the employee. The purpose of this study was to determine the effect of the effectiveness of the use, trust and quality of the accounting information system on employee performance. The population in this study were employees in the administration field at PT Indonesia Power Unit Pembangkitan Bali. The number of samples obtained by saturated sampling technique is as many as 58 respondents. Data analysis used in this study is a multiple linear regression analysis technique. The results of this study indicate that the effectiveness of the use, trust and quality of accounting information systems has a positive effect on employee performance. Keywords: effectiveness of use, trust, quality, employee performance